Pengaruh pembelajaran IPS berbasis proyek terhadap persepsi konsumsi berkarakter mahasiswa S1 Pendidikan IPS Universitas Negeri Malang - Khofifatu Rohmah Adi; Fatiya Rosyida; Neni Wahyuningtyas (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
This study aims to determine the effect of the project-based learning social studies consumer perceptions of student character. Consumer perception of the character of this research is focused on the consumption of environmentally sound because it was found that the students are less concerned about the environment, especially the cleanliness class. This type of research including quasi experimental, aimed at assessing the effect of an action learning on students' perceptions before and after treatment. Subjects were students of 2015 batch S1 IPS which follows the introductory economics course. The instrument used to measure the consumption of environmentally sound perception using a questionnaire with Likert scale. Based on the homogeneity test the cognitive abilities of students conclusion has a homogeneous character and definitive experimental group and the control is done randomly. This study analyzed SPSS 22.0 for Windows using independent sample T-test. Results of the analysis showed that there were significant differences between the control and experimental class class. Therefore, it can be concluded that the application of project-based learning IPS effect on consumer perceptions of character. In project-based learning allows students trying to construct their own knowledge and actively involved in seeking information so it is expected that students are able to connect theory gained with the existing reality in the environment.Keywords: Project Based Learning, Perception Character consumption http://dx.doi.org/10.17977/um022v1i12016p065